A determination method of dynamics for the utilization of metrological capacities in production processes - Srecko Nikolic (ՀՀ ԳԱԱ հրատ.)
The dynamics of measuring instrument utilization in production processes determined by two methods is viewed. The volume of utilization of metrological capacities in production processes influences the realized quality of the product. Դիտարկվում է արտադրության գործընթացում չափիչ սարքերի օգտագործման դինամիկան՝ երկու մեթոդներով: Արտադրության գործընթացում չափագիտական բեռնվածքների օգտագործումն ազդում է արտադրանքի որակի վրա: Рассматривается динамика использования измерительных приборов в процессе производства, описанная двумя методами. Объем использования метрологических нагрузок в процессе производства влияет на качество продуции.
Keywords: Technology; Mechanical engineering and machinery